Effects of Antioxidant Activity and Lipid Lowering Properties of Dates (Pheonix Dactylifera L.) from Libya on Cholestrol-Fed Rabbits - Ab. Hasan, Nawal Salem (2011)
Cardiovascular diseases (CVD) are number one cause of death globally and are expected to remain as the leading cause of death in 2015. According to World Health Organization (WHO), one of the most prominent underlying pathology of CVD is atherosclerosis. The aim of this study is to evaluate the anti-oxidative and lipid-lowering effect of dates (Phoenix Dactylifera-L) flesh aqueous extract, on hypercholesterolemic induced rabbit. The in vitro study was conducted to determine the total antioxidant activity of dates aqueous extract. The scavenging activity of dates was measured using 1-diphenyl-2-picrylhydrazyl (DPPH) method and iron (3) reduction (FRAP) assay. The Total Phenolic Content (TPC) of the date was measured using the Folin-Ciocalteau method. Experimental design used adult male New Zealand white rabbits (seven animals/group) with an average body weight of 2.2-2.8 kg. Following one week acclimatization, the animals were segregated into seven groups as the following: Normal control group, Hypercholesterolemic control group, Simvastatin group and Four treatment groups. The study was designed for 10 weeks and 20ml of ear lobe venous blood samples were taken at 0 week, 5 week, and 10 week, plasma samples obtained were analysed for biochemical measurements. The whole aortas were excised for macroscopy and microscopy studies. The proximate composition of date was found to be high in carbohydrates, total sugar, minerals and vitamins; and a relatively low content of protein, ash and soluble and insoluble dietary fibers. The date sample exhibited lower free radical scavenging activity (87.66%) than the BHT, however the FRAP value obtained for date sample (13.46 mmol/L) was comparable to those of vitamin C and BHT (13.73 mmol/L and 13.75mmol/L) respectively. The supplementation of 125 and 250 mg/kg/day of date extract reduced plasma total cholesterol (TC), low-density lipoprotein (LDL) and triglycerides (TG) levels concomitantly groups supplemented with date extract (T125, T250, T500 and T1000) were significantly higher (P<0.05) in high density lipoprotein (HDL) in diet of induced hypercholesterolemic rabbit. The atherogenic index (AI) and sdLDL values were found to be lower in date extract treated groups compared to ypercholesterolemia group (HC) (P<0.05).A significant reduction of lipid peroxidation (LPO) index indicated with low MDA levels(P<0.05) in groups treated with date extract compared to HC group. At week 10, groups treated with date extract (T125, T250, T500 and T1000) were significantly higher (P<0.05) in total antioxidant activity compared to HC group. No foam cell formation was visible in the aorta of rabbits in groups NC and T250. However, there was visible foam cell formation in the aorta of groups HC, SC, T125, T500 and T1000. In conclusion, results showed that supplementation of 250 mg/kg of dates extract would be able to reduce or retard the progression of atherosclerotic plaque development induced by dietary cholesterol. The enhanced serum HDL, increase in antioxidant status and flavonoids composition may be the possible underlying mechanism of antiatherogenic effect of dates.